Carbon-based coatings doped by copper: Tribological and mechanical behavior in olive oil lubrication - Balestra, R. M. (2011)
We deposited C-based films doped with Cu and tested their sliding properties in olive oil as environment-friendly lubricant, which can be used in many mechanical systems, particularly in agriculture engineering. The coatings were deposited in a four unbalanced magnetron sputtering device combining C and C/Cu targets; argon (hydrogen-free films) and Ar/CH4 (hydrogenated films) atmospheres were used. Cu content of the films was in the range 5-14 at.%. The hardness of the films was almost constant whatever the Cu content was. On the other hand, hydrogen-free coatings were much harder (about 15 GPa) than hydrogenated ones (about 4 GPa). The coatings were oleophilic and their sliding properties were evaluated using ball-on-plate tests with 200000 cycles. The non-hydrogenated coating with 6 at.% of copper showed the best tribological performance with negligible wear for all olive oil testing temperatures (i.e. up to 120 °C).